Gender comparison of RPE at absolute and relative physiological criteria - Robertson, R. J.; Moyna, N. M.; Sward, K. L.; Millich, N. B.; Goss, F. L.; Thompson, P. D. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The effect of gender on ratings of perceived exertion for the overall body (RPE-O), chest (RPE-C), legs (RPE-L), and arms (RPE-A (ski)) was determined.